PROBLEMS IN THE THERAPY OF AXIAL SPONDYLOARTHRITIS IN THE PROCEEDINGS OF THE EULAR CONGRESS 2015 (ROME, 10–13 JUNE 2015) - O. A. Rumyantseva; Sh. F. Erdes (Научно-практическая ревматология, 2016)
The Congress considered the issues pertinent  to the latest approaches to therapy for axial spondyloarthritis  (axSpA), as well as the problems associated with a search for axSpA-modifying anti-rheumatic drugs. Reports on the results of therapy with nonsteroidal  anti-inflammatory drugs and biological agents (tumor necrosis factor-α  and interleukin 17/23 inhibitors) were of the most relevance.